Excisional Biopsy of the Pyogenic Granuloma in Very High-Risk Patient - Dirceu Tavares Formiga Nery; José Ranali; Darceny Zanetta Barbosa; Helvécio Marangon Júnior; Rafael Martins Afonso Pereira; Patrícia Cristine de Oliveira Afonso Pereira (Case Reports in Dentistry)
Oral surgery to remove pyogenic granuloma in a high-risk patient is reported. A 47-year-old man with gastroesophageal reflux disease, diabetes mellitus II, dyslipidemia, and chronic coronary insufficiency (myocardial infarction within 2 years) with episodes of unstable angina was submitted to an excisional biopsy of hemorrhagic lesion in the lingual right mandibular gingiva. During dental treatment, the arterial blood pressure, oxygen saturation, heart rate, and electrocardiogram were monitored. Local anesthesia was performed with 0.45 ml of 3% prilocaine with 0.03 IU/ml felypressin. The anticoagulant therapy was not interrupted. No local or systemic complications were noticed during or after the surgery.